Black carbon emission and transport mechanisms to the free troposphere at the La Paz/El Alto (Bolivia) metropolitan area based on the Day of Census (2012). (December 2018) - Wiedensohler, A.; Andrade, M.; Weinhold, K.; Müller, T.; Birmili, W.; Velarde, F.; Moreno, I.; Forno, R.; Sanchez, M.F.; Laj, P.; Ginot, P.; Whiteman, D.N.; et al.
Abstract: Urban development, growing industrialization, and increasing demand for mobility have led to elevated levels of air pollution in many large cities in Latin America, where air quality standards and WHO guidelines are frequently exceeded. The conurbation of the metropolitan area of La Paz/El Alto is one of the fastest growing urban settlements in South America with the particularity of being located in a very complex terrain at a high altitude. As many large cities or metropolitan areas, the metropolitan area of La Paz/El Alto and the Altiplano region are facing air quality deterioration. Long-term measurement data of the equivalent black carbon (eBC) mass concentrations and particle number size distributions (PNSD) from the Global Atmosphere Watch Observatory Chacaltaya (CHC; 5240 m a.s.l., above sea level) indicated a systematic transport of particle matter from the metropolitan area of La Paz/El Alto to this high altitude station and subsequently to the lower free troposphere. To better understand the sources and the transport mechanisms, we conducted eBC and PNSDs measurements during an intensive campaign at two locations in the urban area of La Paz/El Alto from September to November 2012. While the airport of El Alto site (4040 m a.s.l.) can be seen as representative of the urban and Altiplano background, the road site located in Central La Paz (3590 m a.s.l.) is representative for heavy traffic-dominated conditions. Peaks of eBC mass concentrations up to 5 μg m −3 were observed at the El Alto background site in the early morning and evening, while minimum values were detected in the early afternoon, mainly due to thermal convection and change of the planetary boundary layer height. The traffic-related eBC mass concentrations at the road site reached maximum values of 10–20 μg m −3 . A complete traffic ban on the specific Bolivian Day of Census (November 21, 2012) led to a decrease of eBC below 1 μg m −3 at the road site for the entire day. Compared to the day before and after, particle number concentrations decreased by a factor between 5 and 25 over the particle size range from 10 to 800 nm, while the submicrometer particle mass concentration dropped by approximately 80%. These results indicate that traffic is the dominating source of BC and particulate air pollution in the metropolitan area of La Paz/El Alto. In general, the diurnal cycle of eBC mass concentration at the Chacaltaya observatory is anti-correlated to the observations at the El Alto background site. This pattern indicates that the traffic-related particulate matter, including BC, is transported to higher altitudes with the developing of the boundary layer during daytime. The metropolitan area of La Paz/El Alto seems to be a significant source for BC of the regional lower free troposphere. From there, BC can be transported over long distances and exert impact on climate and composition of remote southern hemisphere. Highlights: The nation-wide traffic ban during the national Day of Census in Bolivia. Traffic counts for 80% of the total particle mass concentration. Diurnal cycle of BC at the Alti Plano with noon minimum due to thermal convection. BC at Chacaltaya shows the opposite behavior with a maximum at noon. Indication of transport of traffic-related BC into the lower free troposphere.